Analysis of Instructional Questions in an English Textbook For Senior High Schools - Usman Kasim; Teuku Zulfikar; Zaiturrahmi Zaiturrahmi (English Education Journal, 2017)
This study aimed to analyze the extent of instructional questions for listening, reading, speaking, and writing activities in the course book, Bahasa Inggris SMA/MA/SMK/MAK Kelas 1 Semester1 emphasizing HOTS (High Order Thinking Skills) or LOTS (Low Order TS); and to investigate the most dominant cognitive dimension of the instructional questions in that textbook. Content analysis was applied for all 9 chapters of the textbook in order to answer the research questions.  All the activities in the form of listening, reading, speaking and writing in the textbook became the object of analysis. Additionally, every instructional question defined as wh- question, yes/no question, multiple choice question, statement question, and true/ false question was taken as the units for analysis. The instructional questions were collected, listed, and analyzed according to Bloom's Taxonomy of cognitive domains. The researcher then calculated the percentage and frequencies of the questions on every level of cognition that appeared in each chapter of the textbook. Descriptive statistics was used to describe the basic features of the data in this study. The results showed that there were 227 instructional questions for listening, reading, speaking, and writing activities. Listening activities had the least instructional questions (11 questions); while the most dominant ones were found for reading activities (125); speaking and writing were in the middle with average frequencies (45 and 46). After the instructional questions in all the activities were categorized, it revealed that most of those instructional questions emphasized LOTS (198 questions).